2020 IEEE Real-Time and Embedded Technology and Applications Symposium (RTAS) 2020
DOI: 10.1109/rtas48715.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Programmable Logic in the Middle: Cache Bleaching

Abstract: Consolidating hard real-time systems onto modern multi-core Systems-on-Chip (SoC) is an open challenge. The extensive sharing of hardware resources at the memory hierarchy raises important unpredictability concerns. The problem is exacerbated as more computationally demanding workload is expected to be handled with real-time guarantees in nextgeneration Cyber-Physical Systems (CPS). A large body of works has approached the problem by proposing novel hardware redesigns, and by proposing software-only solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This next experiment demonstrates the suitability of Enzian for prototyping custom memory controllers, such as PBerry [9], general physical memory manipulation, e.g., Cache Bleaching [58], as well as more general near-data processing. We demonstrate offloading a compute-intensive data reduction task: the colorspace transform and quantization part of a computer vision pipeline.…”
Section: The Fpga As a Custom Memory Controllermentioning
confidence: 98%
See 1 more Smart Citation
“…This next experiment demonstrates the suitability of Enzian for prototyping custom memory controllers, such as PBerry [9], general physical memory manipulation, e.g., Cache Bleaching [58], as well as more general near-data processing. We demonstrate offloading a compute-intensive data reduction task: the colorspace transform and quantization part of a computer vision pipeline.…”
Section: The Fpga As a Custom Memory Controllermentioning
confidence: 98%
“…[18]) integrate CPU cores onto an FPGA die. Access to the cache protocol on the chip in these systems allows a use-case not possible with Intel HARP: the FPGA acting as part of the CPU's memory system, enabling research into new remote memory protocols [8,9] and cache management [58]. However, such systems are tiny in comparison with server machines, typically using 4 low-power ARM cores with limited DRAM.…”
Section: The Changing Fpga Platform Landscapementioning
confidence: 99%
“…Traditionally, in PS-PL platform, the PL-side is used to map hardware accelerators that work in a load-unload fashion. However, Roozkhosh et al [58] have prompted a shift in paradigm with the introduction of the Programmable Logic in the Middle (PLIM) approach. This approach differentiates itself from the others in light of the way it considers and uses the PL-side.…”
Section: Programmable Logic In the Middlementioning
confidence: 99%
“…This capability of inspecting memory traffic at the granularity of individual transactions has already been leveraged to address and tackle bedeviling problems. For instance, PLIM demonstrates how by simply manipulating each transaction address, memory fragmentation introduced by address coloring can be mitigated [58]. The same authors have also shown that the same type of module can be integrated in a wider framework in order to address the problem of memory traffic scheduling [33].…”
Section: Programmable Logic In the Middlementioning
confidence: 99%
See 1 more Smart Citation